Monetary policy rules and external shocks an a semi-dollarized economy - Dancourt, Oscar (2013)
The 2008-2009 crisis showed that the main macroeconomic challenge facing an economy such as Peru's is the management of external shocks that deteriorate the balance of payments and reduce aggregate demand. The aim of this paper is to discuss what the monetary policy response to theseexternal shocks should be. Since inflation targeting was implemented in 2002, the most important instrument of Peruvian monetary policy has been a short-term interest rate. Another key instrument of monetary policy has been sterilized intervention in the foreign exchange market. In order to compare the different monetary policy responses to external shocks, these central bank instruments are incorporated into a textbook IS-LM-BP model. This model is adapted to the financial conditions of an economy such as Peru’s, which has a banking system that operates in both domestic and foreign currency.The conclusion of this paper, in keeping with that of Blanchard et al. (2010), is that a monetary policy which combines a Taylor rule for setting the interest rate, aimed at internal equilibrium, with a foreign exchange intervention policy of leaning against the wind, aimed at external equilibrium, can stabilize both price levels and economic activity in the face of external shocks.The central bank should reduce the interest rate and sell foreign currency to face adverse external shocks, and should raise the interest rate and buy foreign currency to face favorable external shocks.